Factors associated with mobility of the oldest old - Santos, Vanessa Ribeiro Dos (2017)
AbstractIntroduction:Several factors can be associated to the reduction of mobility among the elderly. Early identification of these factors is crucial, since it may lead to prevention of functional dependencies.Objective:To analyze the association between mobility, sociodemographic factors and the prevalence of noncommunicable chronic diseases (NCDs) in oldest old.Methods:The sample consisted of 120 elderly persons aged (80 and 95 years), with 76 of them being women (83 ± 3 years) and 44 of them men (83 ± 3 years). Sociodemographic factors and NCDs which we studied were: age, gender, marital status, education, nutritional status, ethnicity, hypertension, diabetes and osteoarticular diseases. Mobility was analyzed using a battery of Physical Performance Tests. For statistical analysis we used the chi-square test and binary logistic regression to examine the relationship between sociodemographic factors, NCDs and mobility. SPSS (17.0) software was used for this and the significance level was set at 5%.Results:Level of education (p ≤ 0.001) and age (p = 0.034) are the two factors related to low mobility. However, the model built by multiple logistic regression analysis revealed that age is independently related to limited mobility in oldest old people (OR 3.29; 95% CI 1.09 to 9.87).Conclusion:Thus, oldest old >85 years are at a greater risk of decreased mobility independent of their education, marital and nutritional statuses and gender. We encourage further studies in this area. Studies which will not only address those facts considered in this study but that also examine family-related aspects, especially using longitudinal studies.